Decoding success metrics: a deep dive into the integration of technology and key performance indicators for sales optimization at Square Toiletries Limited - Anonna, Khadizatul Kubra (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.